The impact of climate change on the geographical distribution of habitat-forming macroalgae in the Rías Baixas. (October 2020) - Des, M.; Martínez, B.; deCastro, M.; Viejo, R.M.; Sousa, M.C.; Gómez-Gesteira, M.
Abstract: In the current scenario of climate change characterized by a generalized warming, many species are facing local extinctions in areas with conditions near their thermal tolerance threshold. At present, the southern limit of the geographical distribution of several habitat-forming algae of cold-temperate affinities is located in the Northwest Iberian Peninsula, and the Rías Baixas may be acting as contemporary refugia at the range edge. Therefore, it is necessary to analyze future changes induced by ocean warming in this area that may induce changes in macroalgae populations. The Delft3D-Flow model forced with climatic data was used to calculate July–August sea surface temperature (SST) for the present (1999–2018) and for the far future (2080–2099). Mean daily SST was used to develop and calibrate a mechanistic geographical distribution model based on the thermal survival threshold of two intertidal habitat-forming macroalgae, namely Himanthalia elongata (L.) S.F.Gray and Bifurcaria bifurcata R. Ross . Results show that H. elongata will become extinct in the Rías Baixas by the end of the century, while B. bifurcata will persist and may occupy potential free space left by the decline in H. elongata . Highlights: Climate change impact on habitat-forming macroalgae using numerical predictions. Ocean warming will increase the exposure time to heatwaves of macroalgae. H. elongata and similar thermal tolerance macroalgae may become extinct locally. B. bifurcata and similar thermal tolerance macroalgae settlements will be favored. The Rias Baixas will remain as refugia for many species.